Lymphangioleiomyomatosis: a study of 72 patients from the Spanish Registry - Antòn, E.; Casanova, Á.; Xaubet, et al., A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Pulmonary lymphangioleiomyomatosis (LAM) is a rare lung disease that almost exclusively affects young women of childbearing age. The true incidence and prevalence of LAM are unknown. This study was conducted to evaluate the characteristics of lymphangioleiomyomatosis in Spain. Methods: Over a 2- year period, a questionnaire designed for this study was collected. This questionnaire included sociodemograhic, clinical, radiological and functional data. Information about the study and this questionnaire were both sent by e-mail to all the participants of the interstitial disease registry of 2004. Results: Seventy-two patients, all of whom were women, were included in the registry, with a mean age of 44.56 ± 11.1 yr. Sixty-three patients (87.5%) presented the sporadic LAM and 9 (12.5%) presented LAM associated with tuberous sclerosis (LAMTS). LAM diagnosis was confirmed with an open lung biopsy in 57 patients (79.2%) and was performed with thoracic HRCT compatible with LAM diagnosis in the other 15 cases. The most frequent symptom was dyspnoea (90%) followed by cough (44.4%). Almost 40% of patients presented renal angiomyolipomas in the study and the most frequent spirometric pattern was obstructive in more than half of the patients. Most patients with LAM-TS (88.8%) had renal angiomyolipomas compared with 31.7% in the sporadic LAM group. Conclusion: The characteristics of the Spanish population affected with LAM are similar to those of other countries. Most patients were symptomatic, had a history of previous pneumothorax and presented abnormal radiological findings and pulmonary function tests.